Pastoral marketing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Customary commerce: A historical reassessment of pastoral marketing in Africa by Carol Kerven 19921 119pp ISBN 0 85003 172 9 Pbk UKL8.95 Overseas Development Institute, Regent's College Inner Circle, Regent's Park London NW1 4NS, UK